Knowledge, attitude, and its correlates of the community toward mental illness in Mattu, South West Ethiopia - Jarso, Mohammedamin Hajure; Debele, Gebiso Roba; Gezimu, Wubishet; Nigatu, Desalegn; Mohammedhussein, Mustefa; Mamo, Aman; Dule, Aman; Hassen, Mohammedjud; Jemal, Kiyar (Frontiers in Psychiatry, 2022)
Background: The magnitude of mental health conditions in the general population was high in low-resource settings like Ethiopia. This was accompanied by little evidence on knowledge, attitudes, and related determinants in the general population. Therefore, the current survey is planned to assess the knowledge, attitude, and related factors of the community toward mental illness in Mattu, Southwest Ethiopia. Objectives: A study aimed to assess the knowledge, attitude, and related factors of the community toward mental illness in Mattu, Southwest Ethiopia. Methods: A community-based cross-sectional survey was conducted in southwest Ethiopia, Mattu town from April 1-June 20, 2022 using a multistage stratified technique from 649 households. Epi-data Version 3.1 and SPSS-V-23.3 were employed for data entry and analysis respectively. A statistically significant association was declared at a P-value ≤ 0.05 at a 95% confidence interval. Results: In the current study, poor knowledge and unfavorable attitudes towards mental illness among study respondents were 28% (182) 95% CI (24.3, 31.6) and 60.4% (392) 95% CI (56.5, 64.3), respectively. After controlling for potential confounders, being self-employed was independently associated with poor knowledge [AOR = 3.1, 95%CI (1.65, 4.28)]. Moreover, current use of substances [AOR = 1.64 95%CI (1.09, 5.98)] and not hearing information about mental illness from social media has been shown to have association in the final model with an unfavorable attitude [AOR = 3.44 95%CI (1.98, 5.99)]. Conclusion and recommendation: About one-third and more than one-half of the study participants showed poor knowledge and an unfavorable attitude, respectively. Compared to similar global and local findings, there was better community knowledge and a poor attitude toward mental illness in the area. Unfavorable attitudes toward mental illness were found to be exacerbated by not hearing about it on social media and current substance use. Moreover, being self-employed was independently associated with poor knowledge of mental illness. Hence, all concerned stakeholders have to enhance mental health advocacy to improve public knowledge and attitude towards mental illness through media campaigns with a special focus on common substances. In addition, due attention be given for self-employed groups of society to reduce the impacts of mental health conditions.